Analisis Kepadatan Titik dan Geometri Mesh 3D pada Bangunan Gedung Gebouw Van Padangsche Spaarbank - Ikhlasul Amal; Fajrin Fajrin; Defwaldi Defwaldi (Pusat Riset dan Inovasi Nasional, 2024)
Cultural heritage archiving by collecting and managing archives that include documents, archiving using the Close Range Photogrammetry method by analyzing the density of points and making a 3D model of the Gebouw Van Padangsche Spaarbank building by taking overlapping photo data from different camera angles. The purpose of this study is to analyze the point density and geometry of the 3D mesh to create an archive, improving efficiency in information management. In this study, the results of 3D modeling of the Gebouw Van Padangsche Spaarbank building with a close-range photogrammetry technique were obtained, resulting in 157 photos used to make 3D models. The flying altitude of the drone is not more than 20 m with the height of each line varies, for Line 1 is at the top line at an altitude of 17 m, Line 2 is at an altitude of 10 m, Line 3 is at an altitude of 17 m, height is 7 m and for Line 4 at an altitude of 3 m The results obtained from this analysis are 94,869 tie points from the results of 144,764, thick clouds 15,393,722, and faces 529,237. The results of the comparison of the dimensional accuracy test of the 3D model building to the actual size in the field resulted in an average distance of 0.1408 m.